Factors Affecting Occurrence of Depression in Patients with Cervical Cancer at Dr. Moewardi Hospital Surakarta, Central Java: A Path Analysis Model - Dewi Shinta; Didik Gunawan Tamtomo; RB Soemanto (Journal of Epidemiology and Public Health, 2019)
Background: Cervical cancer is in the second place among the incidence of new cases and in thethird highest death from cancer. Cancer depression and severity generally occur together with psychological problems, such as anxiety, pain and fatigue. Most studies in cancer patients have focused on morbidity or mortality more due to the risk of depression. The purpose of this study was to analyze the factors that influence depression in cervical cancer patients.Subjects and Method: A cross sectional study was conducted at Dr. Moewardi Hospital, Surakarta, Central Java, from September to October 2019. A sample of 200 cervical cancer patients was selected by simple random sampling. The dependent variable was depression. The independent variables were marital status, education, occupation, family income, peer support, family support, health personnel support, coping strategy, cancer stage, frequency of chemothe